Pembangunan Hukum dan Hak Asasi Manusia di Indonesia - Darnela, Lindra (Al-Manahij: Jurnal Kajian Hukum Islam, 2009)
There are some changes towards law protection of human rights. UUD 1945 is not as accommodative as RIS constitution. To overcome the problems, the government made an amendment to UUD 1945 section 28, to give more law protection for human right.